He's got the whole world in his hands - Nelson, Kadir (New York : Dial Books for Young Readers, 2005)
An illustrated version of the well-known song that began as a spiritual and is now sung in churches, camps, schools, and has been recorded by opera singers, country artists, and children's performers.
Keywords: Spirituals (Songs) -- Texts; Children's songs, English -- United States -- Texts; Spirituals (Songs); Songs; Children's songs, English; Songs; Spirituals (Songs); United States; Texts